Exploring the Median Effective Dose of Ciprofol for Anesthesia Induction in Elderly Patients: Impact of Frailty on ED50 - Yuan J; Liang Z; Geoffrey MB; Xie Y; Chen S; Liu J; Xia Y; Li H; Zhao Y; Mao Y; Xing N; Yang J; et al. (Dove Medical Press, 2024)
Jingjing Yuan,1,2,* Zenghui Liang,1,* Muhoza Bertrand Geoffrey,1 Yanle Xie,1,2 Shuhan Chen,1,2 Jing Liu,1,2 Yuzhong Xia,1 Huixin Li,1 Yanling Zhao,1 Yuanyuan Mao,1,2 Na Xing,1,2 Jianjun Yang,1,2 Zhongyu Wang,1 Fei Xing1,2 1Department of Anesthesiology, Pain and Perioperative Medicine, the First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan Province, People's Republic of China; 2Henan Province International Joint Laboratory of Pain, Cognition and Emotion, Zhengzhou, Henan Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Fei Xing; Zhongyu Wang, Department of Anesthesiology, Pain and Perioperative Medicine, the First Affiliated Hospital of Zhengzhou University, No. 1 Jianshe East Road Erqi District, Zhengzhou City, Henan Province, People's Republic of China, Tel +86-15936275656, Email fccxingf@zzu.edu.cn; wzy781217@163.comPurpose: Explore the median effective dose of ciprofol for inducing loss of consciousness in elderly patients and investigate how frailty influences the ED50 of ciprofol in elderly patients.Patients and Methods: A total of 26 non-frail patients and 28 frail patients aged 65- 78 years, with BMI ranging from 15 to 28 kg/m2, and classified as ASA grade II or III were selected. Patients were divided into two groups according to frailty: non-frail patients (CFS< 4), frail patients (CFS≥ 4). With an initial dose of 0.3 mg/kg for elderly non-frail patients and 0.25 mg/kg for elderly frail patients, using the up-and-down Dixon method, and the next patient's dose was dependent on the previous patient's response. Demographic information, heart rate (HR), oxygen saturation (SpO2), mean blood pressure (MBP), and bispectral index (BIS) were recorded every 30 seconds, starting from the initiation of drug administration and continuing up to 3 minutes post-administration. Additionally, the total ciprofol dosage during induction, occurrences of hypotension, bradycardia, respiratory depression, and injection pain were recorded.Results: The calculated ED50 (95% confidence interval [CI]) and ED95 (95% CI) values for ciprofol-induced loss of consciousness were as follows: 0.267 mg/kg (95% CI 0.250- 0.284) and 0.301 mg/kg (95% CI 0.284- 0.397) for elderly non-frail patients; and 0.263 mg/kg (95% CI 0.244- 0.281) and 0.302 mg/kg (95% CI 0.283- 0.412) for elderly frail patients. Importantly, no patients reported intravenous injection pain, required treatment for hypotension, or experienced significant bradycardia.Conclusion: Frailty among elderly patients does not exert a notable impact on the median effective dose of ciprofol for anesthesia induction. Our findings suggest that anesthesiologists may forego the necessity of dosage adjustments when administering ciprofol for anesthesia induction in elderly frail patients.Keywords: ciprofol, median effective dose, elderly patients, frailty, loss of consciousness